If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -1q = 8 Solving 12 + -1q = 8 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -1q = 8 + -12 Combine like terms: 12 + -12 = 0 0 + -1q = 8 + -12 -1q = 8 + -12 Combine like terms: 8 + -12 = -4 -1q = -4 Divide each side by '-1'. q = 4 Simplifying q = 4
| x+7/3=7 | | (2/7)=(x/-42) | | -4-x=6x-4 | | y-8+6y=-9+5y+1 | | 12=e/12 | | 7x+8=8+6x | | 4x+11=5x+4 | | x+1.35=2 | | -4/7-1/2v=-2/3 | | 3w=4w+-10 | | (7/10)*(4/5) | | 3-4x=2x+21 | | (x/4)=(3/2) | | 44=28-4(x-2) | | 5/14=p/49 | | 5x+10=-100 | | -4x+7=-6x+17 | | E/12=13 | | 20-d=13 | | 15-3y+2=5 | | 4((x^2)-6x+9)=192 | | 8.5-32=-82 | | 1/4(x-4)=-4 | | 32x^2+56x+12= | | -6x-6=6x+126 | | -2[3(x-5)-2(3x+2)]=10 | | -6(u+1)=8u-7+2(2u+8) | | 14m-10=3(4+m)+11m | | -2[11+2(k-4)-3k+1]=k-4 | | -3+4x=6x+19 | | X^2-5x-4=-9 | | 4/5x-1=11 |